Solving the carbon-dioxide buoyancy challenge: The design and field testing of a dissolved CO2 injection system. (June 2015) - Sigfusson, Bergur; Gislason, Sigurdur R.; Matter, Juerg M.; Stute, Martin; Gunnlaugsson, Einar; Gunnarsson, Ingvi; Aradottir, Edda S.; Sigurdardottir, Holmfridur; Mesfin, Kiflom; Alfredsson, Helgi A.; Wolff-Boenisch, Domenik; Arnarsson, Magnus T.; et al.
Highlights: More than 170 t of water dissolved CO2 was injected to a depth of 400–800 m. The injection was verified by both subsurface fluid chemistry and direct observation. This method results directly to solubility storage of CO2 during injection. This method facilitates the 'in situ' carbonation of the injected gas. Abstract: Long-term security is critical to the success and public acceptance of geologic carbon storage. Much of the security risk associated with geologic carbon storage stems from CO2 buoyancy. Gaseous and supercritical CO2 are less dense than formation waters providing a driving force for it to escape back to the surface via fractures, or abandoned wells. This buoyancy can be eradicated by the dissolution of CO2 into water prior to, or during its injection into the subsurface. Here we demonstrate the dissolution of CO2 into water during its injection into basalts leading directly to its geologic solubility storage. This process was verified via the successful injection of over 175 t of CO2 dissolved in 5000 t of water into porous rocks located 400–800 m below the surface at the Hellisheidi, Iceland CarbFix injection site. Although larger volumes are required for CO2 storage via this method, because the dissolved CO2 is no longer buoyant, the storage formation does not have to be as deep as for supercritical CO2 and the cap rock integrity is less important. This increases the potential storage resource substantially compared to the current estimated storage potential of supercritical CO2 .